1981
DOI: 10.1016/s0196-0644(81)80008-x
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol overdose

Abstract: We report the first two documented cases of the deliberate metoprolol overdose occurring in the United States, one of which eventually proved fatal. The potentially lethal cardiotoxic effects of this drug are illustrated and correlated with the blood and tissue levels of metoprolol. We emphasize the often sudden and rapid clinical deterioration which excessive ingestion of this drug may produce, and the need for close, careful supervision and monitoring of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Metoprolol, in particular, causes rapid deterioration, as supported by our case, consistent with previous reports demonstrating symptom development of immediaterelease formulations occurring within 2 hours post-ingestion time [4][5][6]. Although the patient's comprehensive toxicologic screening examination detected either atenolol or metoprolol, after discussion with toxicology laboratory staff, this was due to the similar molecular structure of the drugs, as quantitative send out measures of metoprolol were significantly elevated.…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 90%
See 1 more Smart Citation
“…Metoprolol, in particular, causes rapid deterioration, as supported by our case, consistent with previous reports demonstrating symptom development of immediaterelease formulations occurring within 2 hours post-ingestion time [4][5][6]. Although the patient's comprehensive toxicologic screening examination detected either atenolol or metoprolol, after discussion with toxicology laboratory staff, this was due to the similar molecular structure of the drugs, as quantitative send out measures of metoprolol were significantly elevated.…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 90%
“…Overdose signs and symptoms include bradycardia; hypotension; bronchospasm; myocardial infarction; cardiac failure; and, eventually, death [2]. Metoprolol distributes rapidly between blood and extravascular sites, causing sudden and rapid deterioration [4,5]. A retrospective review of patients suffering from β-adrenergic antagonist toxicity found that all 39 patients developed symptoms within 6 hours, the majority developing symptoms 2 hours after ingestion [6].…”
mentioning
confidence: 99%
“…Following metoprolol overdosage (Moller 1976;Sire 1976), normal sinus rhythm is usually maintained despite hypotension, as in a case reported by Shore et al (1981) with a plasma concentration of 63 mg/L, Profound bradycardia has been reported in the near terminal stages of metoprolol poisoning (Shore et al 1981;Wallin & Hulting 1983), but then it was probably due to secondary factors such as hypoxia and acidosis. However, metoprolol does have a small degree of membrane depressant activity which may contribute to toxicity.…”
Section: Sotalolmentioning
confidence: 94%
“…2.5 to 10~g/kg/min) is very limited and the few reports give conflicting accounts of its efficacy (Shore et al 1981 tried, but usually with little success (Weinstein 1984). Experience with dobutamine (e.g.…”
Section: Specific Therapiesmentioning
confidence: 99%
“…Glucagon is considered a first line vasopressor in this setting due to its ability to increase intracellular cyclic AMP via a non-catecholamine receptor on the cell wall (2,3). The ability of glucagon to reverse β-blocker toxicity is variable, however, and has failed as a single agent in several case reports (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%